2005
DOI: 10.1128/iai.73.1.563-572.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Roles of HtrA-Like Surface Proteases in Two Virulent Staphylococcus aureus Strains

Abstract: The HtrA surface protease is involved in the virulence of many pathogens, mainly by its role in stress resistance and bacterial survival. Staphylococcus aureus encodes two putative HtrA-like proteases, referred to as HtrA 1 and HtrA 2 . To investigate the roles of HtrA proteins in S. aureus, we constructed htrA 1 , htrA 2 , and htrA 1 htrA 2 insertion mutants in two genetically different virulent strains, RN6390 and COL. In the RN6390 context, htrA 1 inactivation resulted in sensitivity to puromycin-induced st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 48 publications
1
63
0
Order By: Relevance
“…In Staphylococcus aureus COL, the deletion of htrA led to minimal changes in surface protein expression and virulence (73). In Brucella abortus, the htrA mutant was not found to be attenuated in a BALB/c mouse model (74).…”
Section: Discussionmentioning
confidence: 99%
“…In Staphylococcus aureus COL, the deletion of htrA led to minimal changes in surface protein expression and virulence (73). In Brucella abortus, the htrA mutant was not found to be attenuated in a BALB/c mouse model (74).…”
Section: Discussionmentioning
confidence: 99%
“…This gene, designated bhpA, encodes a protein with conserved domains found in a novel class of proteins, the HtrA-like serine proteases (Clausen et al, 2002). In other bacteria, these periplasmic proteases play a key role in the tolerance against various folding stresses (Strauch and Beckwith, 1988) and contribute to pathogenicity (Johnson et al, 1991;Boucher et al, 1996;Miller and Shinnick, 2000;Rigoulay et al, 2005). E. coli has three genes, degP, degQ, degS, that encode proteases in the HtrA family (Lipinska et al, 1988;Waller and Sauer, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This is not the case in Salmonella, but S. Typhimurium htrA mutants exhibit increased sensitivity to killing by reactive oxygen species and reduced survival and/or replication within macrophages (Baumler et al, 1994;Humphreys et al, 1999;Johnson et al, 1991), and are highly attenuated in the murine model of systemic Salmonella infection (Chatfield et al, 1992;Humphreys et al, 1999). Since the seminal studies in Salmonella, HtrA has been found to play a role in the virulence of a wide range of Gram-negative and Grampositive bacterial pathogens (Bringer et al, 2005;Cortes et al, 2002;Humphreys et al, 1999;Ibrahim et al, 2004;Johnson et al, 1991;Jones et al, 2001;Pallen & Wren, 1997;Pedersen et al, 2001;Rigoulay et al, 2005;Williams et al, 2000).…”
Section: Introductionmentioning
confidence: 99%